2008
DOI: 10.1080/10412905.2008.9699430
|View full text |Cite
|
Sign up to set email alerts
|

Vitex ferrugineaSchumach. Et. Thonn. subsp.amboniensis(Gürke) Verdc.: glandular trichomes micromorphology, composition and antifungal activity of the essential oils

Abstract: Publication details, including instructions for authors and subscription information: http://www.tandfonline.com/loi/tjeo20 Vitex ferruginea Schumach. Et. Thonn. subsp. amboniensis (Gürke) Verdc.: glandular trichomes micromorphology, composition and antifungal activity of the essential oils Vitex ferruginea Schumach. Et. Thonn. subsp. amboniensis (Gürke) Verdc.: glandular trichomes micromorphology, composition and antifungal activity of the essential oils AbstractThe morphology and distribution of the glandula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Among them, it is commonly used in the treatment of menstrual disorders resulting from corpus luteum de�ciency, including premenstrual symptoms and spasmodic dysmenorrheal, for certain menopausal conditions, for insufficient lactation, and for the treatment of acne [5,6]. e fruits, �owers, and leaves of Vitex agnus-castus L. are reported to contain phenolic acids and their derivatives, �avonoids, tannins, iridoids, diterpenoids, and essential oil composition [7][8][9][10]. Juniperus oxycedrus L. is one of the most widespread species of the genus, with a range extending from Africa and the Iberian Peninsula, throughout Mediterranean Europe and Anatolia to the Caucasus and Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, it is commonly used in the treatment of menstrual disorders resulting from corpus luteum de�ciency, including premenstrual symptoms and spasmodic dysmenorrheal, for certain menopausal conditions, for insufficient lactation, and for the treatment of acne [5,6]. e fruits, �owers, and leaves of Vitex agnus-castus L. are reported to contain phenolic acids and their derivatives, �avonoids, tannins, iridoids, diterpenoids, and essential oil composition [7][8][9][10]. Juniperus oxycedrus L. is one of the most widespread species of the genus, with a range extending from Africa and the Iberian Peninsula, throughout Mediterranean Europe and Anatolia to the Caucasus and Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Caryophyllene was identified as the major component of four Vitex species which are; V. limonifolia (Thailand) (Suksamrarn al., 1990), V. polygama (Brazil) (Leitao et al, 1999), V. rufescens (Brazil), and V. megapotamica (De Sena Filho et al, 2017). Besides, germacrene D was found in two different Vitex species which are; V. ferruginea (South Africa) (Cabral et al, 2008) and V. rivularis (Cameroon) (Cabral et al, 2009). In addition, the other sesquiterpene hydrocarbons were δ-cadinene (De Sena Filho et al, 2017), cis-calamenene (Vale et al, 2019;Silva et al, 2019;Pereira et al 2018), 6,9-guaiadiene (De Sena Filho et al, 2017, which were found in the leaf oil of Brazillian V. capitata, V. gardneriana, and V. gardneriana, respectively.…”
Section: Chemical Composition Of Vitex Essential Oilsmentioning
confidence: 99%
“…Table 1 shows the medicinal uses of several Vitex species. (Yoganarasimhan, 2000) V. buchananii Leaves To treat venereal diseases (Cabral et al, 2009) V. cannabifolia Fruits To treat analgesia, cough, used as anti-tussive (Yamasaki et al, 2008) V. congolensis Leaves To cure cicatrisation (Cabral et al, 2009) V. diversifolia Barks To cure tooth and skin diseases, headache, intestinal bilharzias (Zerbo et al, 2011) V. doniana Barks To treat gastroenteritis, diarrhea, and dysentery (Kilani, 2006) V. ferruginea Leaves To cure skin diseases, mouth sore, snake-bite (Cabral et al, 2008) V. gaumeri Leaves To treat colds, cough spelling, diarrhea, gastrointestinal affections (Damayanti et al, 1996) V. leucoxylon Leaves To relieve headache, catarac, as a medicinal bath for fever and anemia, reduced cholesterol, antiinflammatory (Makwana et al, 1994) V. lucens Leaves To relieve sprains, backache, treating ear ulcers, sore throats, for dead's people body wash (Dykgraaf, 1992) V. madiensis Leaves To treat skin disease (Cabral et al, 2009) V. madiensis Leaves To prevent malaria (Ondo et al, 2012) Nat. Volatiles & Essent.…”
Section: Medicinal Uses Of the Genus Vitexmentioning
confidence: 99%
See 1 more Smart Citation
“…The oils from glandular trichomes of V. ferruginea exhibited significant antifungal activity against dermatophyte strains with MIC between 0.16 and 0.64 μL/mL. [ 61 ]…”
Section: Introductionmentioning
confidence: 99%